FREQUENCY AND TREATMENT OF URINARY TRACT INFECTION IN CHILDREN SUBJECTED TO URINE CULTURE, IN SANA’A, YEMEN - Mohanna, Mabrook Aidah Bin; Raja, Yahia Ahmed (Journal of Ayub Medical College Abbottabad, 2005)
Background: This study was carried out to estimate the frequency of urinary tract infection among children subjected to urine culture presenting to Sam Hospital, Sana’a city, Yemen and to determine the susceptibility of the isolated bacteria to the antibiotics. Methods: Record-based study was done in Sam Hospital in Sana’a city Yemen during three years 1/ 1/ 1999-31/ 12 / 2001. Out of 70500 patients seen for different causes through that period 820 (1.16%) having urinary symptoms (fever, rigor, vomiting, frequency or screams during the act of urination) were subjected to urine culture. Data about age and sex were also collected. Results: Frequency of urinary tract infections among children examined by urine culture was 36.8% (n=302), with mean age of 7.6 years, 272 (90.1%) of them were females, and 30 (9.9%) were males. More than half 154(51%) of infected patients were less than three year old. The isolated bacteria was Escherichia.coli 201 (66.3 %) followed by Staphylococcus suprofyticus 45 (14.9%, Proteus spp 15 (4.9%), Klebseilla 12 (3.9%) then Enterococcus spp 12 (3.9%). Sensitivity of E. coli, to Nalidexic acid was 70%, to Amoxicillin/Clavulanic acid was 29.9%, to Co-trimoxasole was 16.4%, and to Nitrofurantoin was 15.9%. Conclusion: The majority of the infected patients were females and the highest frequency of the disease was in the first three years of age. The most common isolated microorganism was E.coli followed by Staphylococcus suprofyticus, Proteus spp, then Enterococcus spp. The highly active antibiotic for most organisms isolated was Nalidexic acid, then amoxicillin/ clavulanic acid. Nalidexic acid can be used as a first line empiric treatment and/or prophylaxis of UTI in children. Keywords: Urinary tract infection, children, Yemen.